Prototipo de Software Antiplagio para la Carrera de Ingeniería en Computación de la Universidad Nacional de Loja, utilizando Redes Neuronales - Paqui Medina, Jaime Oswaldo (2025)
Detecting and identify the plagiarism is essential work to avoid the theft of concepts and content. Today there are many tools that allow you to avoid plagiarism, but most are paid and their access is limited, for this motive few users purchase them. For this reason, this Information and Communication Technologies (ICT) has been carried out with the purpose of creating a software prototype aimed at solving the problem, ¿How to control plagiarism by developing anti-plagiarism software for the Computer Science degree at the National University of Loja (UNL), using neural networks? To address this problem, two specific objectives were set, carried out using the XP methodology, which consists of four phases: planning, design, coding and testing. This (ICT) Information and Communication Technologies begin with the first objective of designing the Anti-plagiarism control model using neural networks, therefore the related work TR2 was taken as a starting point, resulting in the implementation of the model. To comply with the second objective for the development of Anti- plagiarism software anti- plagiarism using the Django framework and applying the 4 + 1 model, it was decided to use the requirements specification based on the IEEE830 standard together with the XP methodology, obtaining as a final result the Anti-plagiarism software. Functional tests and acceptance tests were also carried out using the TAM model (technology acceptance model), in order to guarantee the correct functioning of the Anti-plagiarism software and that the established functional requirements are met, in addition to the preparation of user manuals for each role. This way the research question could be answered, confirming that the developed software can control plagiarism in PIC (curricular integration projects), since it way satisfactory results.